AR film and preparation method thereof
By setting the germanium film layer and the zinc sulfide film layer on the polishing sheet in turn and optimizing the thickness ratio, the problem of insufficient transmittance of the existing AR film is solved, and an AR film with high transmittance is achieved, and the performance of optical equipment and display equipment is improved.
Patent Information
- Application Number
- CN202411706940.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the transmittance of the AR film is insufficient, which affects the imaging quality of the optical device and the energy efficiency of the display device.
By sequentially setting the germanium film layer and the zinc sulfide film layer on the polishing surface of the polishing sheet, and optimizing the thickness ratio of the two film layers, the transmittance of the AR film is improved.
A high transmittance AR film is realized, which improves the imaging quality of optical devices and the energy efficiency of display devices.
Smart Images

Figure BDA0005154717480000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical element production, and in particular to an AR film and a preparation method thereof. Background Art
[0002] AR film, or anti-reflection film, is an optical film. Its main function is to reduce the reflection of the optical surface and increase the transmittance of light.
[0003] From a microscopic perspective, AR coating is made by coating the surface of optical components with multiple layers of thin film materials with different refractive indices. The thickness of these films is precisely designed so that within a specific wavelength range, the reflected light interferes with each other, thereby reducing the reflectivity. For example, for a glass surface, when it is not coated, due to the difference in refractive index between glass and air, light will be reflected at the interface, with a reflectivity of about 4%. After coating with AR coating, the reflectivity can be significantly reduced, and the light transmission efficiency can be improved.
[0004] In imaging devices, such as camera lenses, if the transmittance of the AR film on the lens is low, it will cause light loss, thus affecting the brightness and contrast of the image. A high transmittance AR film allows more light to enter the lens, making the photos or videos taken brighter, clearer, and with higher color reproduction. For high-end camera lenses, improving the transmittance of the AR film helps to capture high-quality images in low-light environments.
[0005] In optical instruments such as telescopes and microscopes, increased transmittance means that the target can be observed more clearly. For example, an astronomical telescope needs to observe distant and faint celestial bodies. If the AR film has low transmittance, a lot of light emitted by the celestial body will be lost, making it difficult to obtain accurate astronomical information.
[0006] In display devices, such as liquid crystal displays (LCDs) and organic light-emitting diode displays (OLEDs), low-transmittance AR films will cause a large amount of light from the backlight source to be reflected on the screen surface. In order to achieve sufficient display brightness, the power of the backlight source needs to be increased. Increasing the transmittance of the AR film can reduce light reflection and reduce the energy consumption of the backlight source while ensuring the same display brightness. This helps extend battery life for mobile devices such as mobile phones and tablets.
[0007] On eyeglass lenses, high-transmittance AR films can reduce reflections on the lens surface. When people wear glasses, whether they are myopia glasses, hyperopia glasses or sunglasses, low-reflection lenses can make the wearer's eyes more clearly visible to others, and also allow the wearer to see the surrounding environment more clearly, reducing visual interference caused by lens reflections. Therefore, transmittance has an important meaning and impact on AR films.
[0008] Chinese patent application 201811555428.7 discloses a medium-wave infrared antireflection film on a silicon substrate, which uses germanium (Ge) as a high-refractive index coating material, zinc sulfide (ZnS) and ytterbium fluoride (YbF3) as low-refractive index coating materials, uses PVD method for optical thin film coating, and uses ion source assisted deposition and specific material evaporation process conditions to deposit 5 layers of irregular film on the two surfaces of the substrate. The antireflection film can make the silicon window have excellent light transmission effect in the wavelength range of 3 to 5μm, with an average transmittance of >98%. It can effectively improve the optical efficiency of uncooled infrared focal plane detectors and improve the imaging quality of infrared thermal imagers;
[0009] Further observation of the scheme shows that the film system structure of the front film system (1) in the scheme is:
[0010] Substrate / 0.096M 0.048H 0.331M 0.397L 0.045M / Air.
[0011] The film structure of the back film system (3) is:
[0012] Substrate / 0.096M 0.048H 0.331M 0.397L0.045M / Air.
[0013] Wherein, H represents a Ge film layer with an optical thickness of λ0 / 4, M represents a ZnS film layer with an optical thickness of λ0 / 4, L represents a YbF3 film layer with an optical thickness of λ0 / 4, λ0 is the central wavelength, and the numbers before H, M and L are the thickness ratio coefficients of the film layers;
[0014] Further observation of the scheme shows that, although the scheme discloses that coating a silicon substrate with materials such as germanium and zinc sulfide can improve light transmittance, the material in direct contact with the substrate in the scheme is zinc sulfide material rather than germanium.
[0015] Chinese patent application 201821592676.4 discloses an 8-14 micron infrared bandpass filter for infrared detectors, including a substrate, a front surface film system and a rear surface film system, wherein the substrate is a silicon wafer, the front surface film system is a 48-layer film system formed by superimposing and evaporating germanium Ge material and zinc sulfide ZnS material, and the rear surface film system is a 13-layer film system formed by superimposing and evaporating germanium Ge material and zinc sulfide ZnS material; it has high transmittance in the working band of 8-14μm, and is cut off in other bands. Compared with traditional filters, it has the characteristics of high transmittance and high cutoff depth. When used with infrared detectors, it improves the signal-to-noise ratio of the sensor and its use effect;
[0016] Further observation of the scheme shows that germanium material and zinc sulfide material are used as the film layer of the lens in this scheme. At the same time, the scheme includes a surface film system and a rear surface film system. The surface film system has a total of 48 layers and the rear surface film system has a total of 13 layers. Moreover, both the front surface film system and the rear surface film system are in direct contact with the substrate with the germanium layer. However, the thickness of germanium and zinc sulfide in this scheme is relatively close.
[0017] The problem to be solved by this solution is: how to develop an AR film with good permeability that is different from the prior art in structure and thickness. Summary of the invention
[0018] The purpose of the present application is to provide an AR film, which improves the transmittance of the AR film by sequentially arranging a first film layer and a second film layer on the polishing surface of a polishing sheet, and by optimizing the types of the first film layer and the second film layer and the thickness ratio between the first film layer and the second film layer.
[0019] To achieve the above object, the present application discloses an AR film, the AR film comprising a first film layer and a second film layer arranged in sequence, the first film layer being close to the polishing surface of the polishing sheet, and the second film layer being arranged on the outer surface of the first film layer;
[0020] The first film layer is a germanium layer with a thickness of 90 to 105 nm;
[0021] The second film layer is a zinc sulfide layer with a thickness of 1260-1350 nm.
[0022] Preferably, the polishing wafer is a silicon polishing wafer.
[0023] In addition, the present application also discloses a method for preparing the above-mentioned AR film, wherein a first film layer is plated on the polishing surface of a polishing sheet, and a second film layer is plated on the outer surface of the first film layer.
[0024] Preferably, the method specifically comprises the following steps:
[0025] Step 1: using electron beam evaporation to plate germanium onto the polishing surface of the polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 90 to 105 nm;
[0026] Step 2: zinc sulfide is plated onto the outer surface of the first film layer by flame retardant evaporation to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1260-1350 nm.
[0027] Preferably, both step 1 and step 2 are performed at 60-85°C and the vacuum degree is 2×10 -3 ~4×10 -3 Pa environment.
[0028] Preferably, step 1 is specifically as follows: adding an appropriate amount of germanium powder into a crucible, and using electron beam evaporation to plate germanium onto the polishing surface of the polishing sheet to obtain a polishing sheet plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 90 to 105 nm, and the coating rate is 4 to 6 A / s.
[0029] Preferably, step 2 is specifically as follows: adding an appropriate amount of zinc sulfide powder to a molybdenum boat, and using a vapor barrier evaporation method to plate zinc sulfide to the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1260 to 1350 nm, and the coating rate is 8 to 12 A / s.
[0030] The beneficial effects of this application are:
[0031] Through the above design, the present application obtains an AR film with high transmittance by sequentially arranging the first film layer and the second film layer on the polishing surface of the polishing sheet, and by optimizing the types of the first film layer and the second film layer and the thickness ratio between the first film layer and the second film layer. DETAILED DESCRIPTION
[0032] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] Example 1
[0034] Step 1: Add an appropriate amount of germanium powder into a crucible, and use electron beam evaporation to plate germanium onto the polished surface of a silicon polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 100 nm, and the coating rate is 5 A / s;
[0035] Step 2: Add an appropriate amount of zinc sulfide powder to the molybdenum boat, and use the method of resisting evaporation to plate zinc sulfide on the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1300 nm, and the coating rate is 10 A / s;
[0036] Step 1 and step 2 were both performed at 70°C and the vacuum degree was 3×10 -3 Pa environment.
[0037] Example 2
[0038] Step 1: Add an appropriate amount of germanium powder into a crucible, and use electron beam evaporation to plate germanium onto the polished surface of a silicon polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 105 nm, and the coating rate is 6 A / s;
[0039] Step 2: Add an appropriate amount of zinc sulfide powder to the molybdenum boat, and use the method of resisting evaporation to plate zinc sulfide on the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1260nm, and the coating rate is 8A / s;
[0040] Step 1 and step 2 were both performed at 85°C and the vacuum degree was 2×10 -3 Pa environment.
[0041] Example 3
[0042] Step 1: Add an appropriate amount of germanium powder into a crucible, and use electron beam evaporation to plate germanium onto the polished surface of a silicon polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 90 nm, and the coating rate is 4 A / s;
[0043] Step 2: Add an appropriate amount of zinc sulfide powder to the molybdenum boat, and use the method of resisting evaporation to plate zinc sulfide on the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1350nm, and the coating rate is 12A / s;
[0044] Step 1 and step 2 were both performed at 60°C and the vacuum degree was 4×10 -3 Pa environment.
[0045] Example 4
[0046] The same as Example 1, except that both step 1 and step 2 were performed at 50°C and the vacuum degree was 3×10 -3 Pa environment.
[0047] Example 5
[0048] The same as Example 1, except that both step 1 and step 2 were performed at 95°C and the vacuum degree was 3×10 -3 Pa environment.
[0049] Example 6
[0050] The same as Example 1, except that both step 1 and step 2 were performed at 70°C and the vacuum degree was 1×10 -2 Pa environment.
[0051] Example 7
[0052] Step 1: Add an appropriate amount of germanium powder to a molybdenum boat, and use a barrier evaporation method to plate germanium on the polished surface of a silicon polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 100 nm, and the coating rate is 5 A / s;
[0053] Step 2: Add an appropriate amount of zinc sulfide powder into the crucible, and use electron beam evaporation to plate zinc sulfide on the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1300 nm, and the coating rate is 10 A / s;
[0054] Step 1 and step 2 were both performed at 70°C and the vacuum degree was 3×10 -3 Pa environment.
[0055] Comparative Example 1
[0056] Step 1: Add an appropriate amount of zinc sulfide powder to a molybdenum boat, and use a vapor barrier evaporation method to plate zinc sulfide on the polishing surface of the polishing sheet to obtain a polishing sheet plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 1300 nm, and the coating rate is 10 A / s;
[0057] Step 2: Add an appropriate amount of germanium powder into the crucible, and use electron beam evaporation to plate germanium on the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 100 nm, and the coating rate is 5 A / s;
[0058] Step 1 and step 2 were both performed at 70°C and the vacuum degree was 3×10 -3 Pa environment.
[0059] Comparative Example 2
[0060] Step 1: Add an appropriate amount of germanium powder into a crucible, and use electron beam evaporation to plate germanium onto the polishing surface of the polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 50 nm, and the coating rate is 5 A / s;
[0061] Step 2: Add an appropriate amount of zinc sulfide powder to the molybdenum boat, and use the method of resisting evaporation to plate zinc sulfide on the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, and during the coating process, the thickness of the second film layer is controlled to be 650nm, and the coating rate is 10A / s;
[0062] Step 3: Add an appropriate amount of germanium powder into the crucible, and use electron beam evaporation to plate germanium onto the outer surface of the second film layer (forming a third film layer), and during the coating process, control the thickness of the third film layer to be 50 nm, and the coating rate to be 5 A / s;
[0063] Step 4: Add an appropriate amount of zinc sulfide powder to the molybdenum boat, and use the method of resisting evaporation to plate zinc sulfide on the outer surface of the third film layer to obtain a polished sheet plated with a fourth film layer. During the coating process, the thickness of the fourth film layer is controlled to be 650nm, and the coating rate is 10A / s.
[0064] Step 1, step 2, step 3 and step 4 were all carried out at 70°C and the vacuum degree was 3×10 -3 Pa environment.
[0065] Comparative Example 3
[0066] Step 1: Add an appropriate amount of germanium powder into a crucible, and use electron beam evaporation to plate germanium onto the polishing surface of the polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 467 nm, and the coating rate is 5 A / s;
[0067] Step 2: Add an appropriate amount of zinc sulfide powder to the molybdenum boat, and use the method of resisting evaporation to plate zinc sulfide to the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 933 nm, and the coating rate is 10 A / s.
[0068] Step 1 and step 2 were both performed at 70°C and the vacuum degree was 3×10 -3 Pa environment.
[0069] Performance Testing
[0070] The transmittance of the AR films prepared in the examples and comparative examples at mid-infrared light with a wavelength of 8-14 um and mid-infrared light with a wavelength of 10 um was tested using a Fourier transform infrared spectrometer. The test results are shown in Table 1:
[0071] Table 1
[0072]
[0073] Result analysis:
[0074] 1. It can be seen from Examples 1-3 that when some parameters in the preparation process of the AR film are slightly adjusted, the transmittance of the AR film obtained in Examples 1-3 fluctuates, but the fluctuation range is relatively small;
[0075] 2. Further observation of Example 1 and Example 4-5 shows that when the temperature of the environment in Step 1 and Step 2 is adjusted too much, the transmittance of the AR film obtained in Example 4-5 is lower than that in Example 1. It is speculated that the reason for this phenomenon may be that when the temperature is too low, the mobility of atoms or molecules in the film is poor at a lower temperature during the growth process of the AR film, which may lead to more defects in the film, such as dislocations, holes, etc.; these defects will scatter light, thereby reducing the transmittance;
[0076] When the temperature is too high, high-temperature growth may cause excessive growth of grains in the film, resulting in larger grain interfaces, which will increase light scattering and affect transmittance;
[0077] 3. It can be seen from Examples 6-7 that when Example 6 reduces the vacuum degree of the vacuum environment during the thin film growth process, gases in the air (such as oxygen, water vapor and nitrogen) will penetrate into the growth environment. These impurities may react with the deposited material during the thin film growth process to form opaque compounds or oxides, thereby affecting the optical properties of the thin film and causing a decrease in transmittance;
[0078] Further observation of Example 7 shows that after changing the coating methods of the first film layer and the second film layer, the vacuum degree of Example 7 is lower than that of Example 1. The reason for this phenomenon may be that the coating method of electronic book evaporation is more suitable for the growth of the first film layer with germanium as the raw material, while the barrier evaporation method is more suitable for the growth of the second film layer with zinc sulfide as the raw material;
[0079] 4. It can be seen from Example 1 and Comparative Example 1 that when the order of the first film layer and the second film layer is changed, the transmittance of the AR film prepared in Comparative Example 1 decreases. The reason may be that the optical properties are closely related to the thickness and refractive index of the film layer. When the order of the film layers is changed, the interference effect of light between different layers will change, which may lead to a change in the phase relationship, thereby affecting the transmittance. For certain specific wavelengths of light, the interference effect may no longer be favorable, resulting in a decrease in transmittance.
[0080] Further observation of Comparative Example 2 shows that when the total thickness of the AR film in Comparative Example 2 does not change relative to Example 1, and only the number of layers of the AR film is increased, the transmittance of Comparative Example 2 also decreases relative to Example 1. It can be seen that increasing the number of layers of the AR film may also change the phase relationship of the film and thus cause a decrease in transmittance.
[0081] At the same time, when the total thickness of the film remains unchanged and the thickness of the first film layer is increased and the thickness of the second film layer is reduced, the transmittance of the AR film prepared in Comparative Example 3 decreases relative to that in Example 1. The reason is that the raw materials of the first film layer and the second film layer are germanium and zinc sulfide, respectively. The optical properties of films prepared from different raw materials are different. When the thickness of different film layers is changed, even if the total thickness of the film remains unchanged, it will still affect the transmittance of the AR film.
[0082] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. An AR film, characterized in that: The AR film comprises a first film layer and a second film layer which are arranged in sequence, wherein the first film layer is close to the polishing surface of the polishing sheet, and the second film layer is arranged on the outer surface of the first film layer; The first film layer is a germanium layer with a thickness of 90 to 105 nm; The second film layer is a zinc sulfide layer with a thickness of 1260-1350 nm.
2. The AR film according to claim 1, characterized in that The polishing sheet is a silicon polishing sheet.
3. A method for preparing the AR film according to any one of claims 1 to 2, characterized in that: The first film layer is plated on the polishing surface of the polishing sheet, and the second film layer is plated on the outer surface of the first film layer.
4. The method for preparing an AR film according to claim 1, characterized in that: The specific steps include: Step 1: using electron beam evaporation to plate germanium onto the polishing surface of the polishing wafer to obtain a polishing wafer plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 90 to 105 nm; Step 2: zinc sulfide is plated onto the outer surface of the first film layer by flame retardant evaporation to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1260-1350 nm.
5. The method for preparing an AR film according to claim 4, characterized in that: The temperature of step 1 and step 2 is 60-85°C and the vacuum degree is 2×10 -3 ~4×10 -3 Pa environment.
6. The method for preparing an AR film according to claim 4, characterized in that: The step 1 is specifically as follows: adding an appropriate amount of germanium powder into a crucible, and using electron beam evaporation to plate germanium onto the polishing surface of the polishing sheet to obtain a polishing sheet plated with a first film layer, and during the coating process, the thickness of the first film layer is controlled to be 90 to 105 nm, and the coating rate is 4 to 6 A / s.
7. The method for preparing an AR film according to claim 4, characterized in that: The step 2 is specifically as follows: adding an appropriate amount of zinc sulfide powder into a molybdenum boat, and using a vapor barrier evaporation method to plate zinc sulfide onto the outer surface of the first film layer to obtain a polished sheet plated with the first film layer and the second film layer, thereby completing the preparation of the AR film. During the coating process, the thickness of the second film layer is controlled to be 1260 to 1350 nm, and the coating rate is 8 to 12 A / s.
Citation Information
Patent Citations
A mid-wave infrared antireflection film on a silicon substrate and its preparation method
CN110146943B
Band pass filter for infrared detector
CN208737033U
Infrared cut-off light filtering films on germanium-base parts surface and plating method thereof
CN101067661A
Infrared chalcogenide glass lens plated with carbon-like film as well as preparation method and application of infrared chalcogenide glass lens
CN114249546A
Intermediate infrared two-color optical filter and preparation method thereof
CN114325911A